Perlindungan Hukum Bagi Notaris Dalam Pembuatan Akta Otentik Yang Penghadapnya Menggunakan Identitas Palsu Dalam Perspektif Hukum Intenasional - Hidayah, Farida Nur (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This study aims to analyze the legal protection for notaries in making authentic deeds when the parties appearing use false identities, viewed from the perspective of international law. In carrying out their duties, notaries have an obligation to ensure the truth of the identities of the parties in order to guarantee the validity of the deeds made. However, in some cases, the parties may use false identities, which has the potential to cause legal problems for notaries. This study highlights the forms of legal protection that can be given to notaries in accordance with the provisions of international law and discusses the responsibilities and limitations of notary authority in such situations. The research method used is a normative legal approach, with an analysis of international legal instruments relating to the protection of the notary profession. The results of the study show that although notaries are responsible for the deeds made, there are legal protection mechanisms that can protect notaries from prosecution if it is proven that they have carried out their duties in good faith and in accordance with applicable procedures. Therefore, harmonization of regulations at the national and international levels is needed to ensure that notaries receive adequate protection in carrying out their profession.